Sprayable, Superhydrophobic, Electrically, and Thermally Conductive Coating. Issue 2 (26th April 2020) - Baldelli, Alberto; Ou, Junfei; Barona, David; Li, Wen; Amirfazli, A.
Abstract: A simple to make, multifunctional, heatable, and sprayable superhydrophobic and electrically conductive coating is developed by dispersing carbon nanofibers (CNFs) into a water repelling polymer matrix. The developed coating exhibits an average static and hysteresis contact angles of 160° and 5°, respectively. An electrical conductivity of 1100 S m −1 and a thermal conductivity of 0.001 W m −1 K −1 are obtained with a sample of dimensions: 3 cm × 1 cm × 20 µm. A 12 µm thick coating under an average electric current of 75 mA reaches to a surface temperature of more than 140 °C for a dry coating. The coating when in contact with ice or water (water at 25 °C for 300 h, and at 85 °C for less than an hour) does not show a deterioration of wetting performance. Furthermore, it is shown how this coating can be used to mitigate the ice formation on cold surfaces. The ability of application of the developed coating to various substrates is also shown. Abstract : A simple to make, multifunctional, heatable, and sprayable superhydrophobic and electrically conductive coating is developed. The coating is made of carbon nanofibers dispersed in a polymer matrix. The coating is capable of melting ice and repelling water at the same time reaching temperatures as high as 140 °C for a dry coating.